Media writer’s handbook : - Arnold, George T. (McGraw-Hill, 2009)
Appropriate for media writing courses as either a primary or supplemental text, Media Writer's Handbook is a primer for anyone who really wants to understand the grammatical and stylistic elements of good writing. Long after being a teaching tool in the classroom, it functions as a resource book that students and professionals can place on their desks alongside their dictionaries and stylebooks.